Structural and surface plasmon behavior of Cu nanoparticles using different stabilizers - Singh M.; Sinha I.; Premkumar M.; Singh A.K.; Mandal R.K. (My University, 2025)
Copper nanoparticles (CuNPs) are prepared in aqueous medium with hydrazine hydrate as the reductant. Different stabilizers PVA, PVP and starch are considered. For each stabilizing agent, the effect of concentration of NaOH on the synthesis of CuNPs is investigated. The structural characterization of CuNPs dispersed in aqueous medium has been done with the help of small angle X-ray scattering (SAXS). The SAXS studies demonstrate the formation of spherical NPs with bimodal size distribution. The primary (smaller) particles/clusters aggregate to form the larger nanoparticles. The scattered intensity after Guinier regime displays fractal behavior. An attempt has been made to understand the effect of stabilizer and NaOH concentration on the formation of such fractal aggregates. Correlations have been drawn between the particles size distribution in the sol and the localized surface plasmon resonance (LSPR) behavior of such CuNPs in aqueous solution. Dominance of smaller nanoparticles (∼5 nm or less) in the sol leads to suppression of the LSPR. © 2010 Elsevier B.V. All rights reserved.